(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the characteristics of sexual dysfunction in infertile female patients with uterine pathology in Thai Nguyen A Hospital, during the period of 2023-2024. Subjects and Methods: This cross-sectional descriptive study involved 85 wives from infertile couples with uterine pathology, who were first-time visitors to Thai Nguyen A Hospital. The study utilized the Female Sexual Function Index - FSFI-19 questionnaire. Results: Common uterine pathologies included polyps (34.7%), Uterine fibroids (20.0%), endometriosis (18.8%), and endometrial hyperplasia (12.9%). The average FSFI score among the wives was 26.1 ± 4.9 (4.0 – 34.8), with 52 cases accounting for 61.2% experiencing sexual dysfunction. The rates of decreased sexual desire, arousal, lubrication, orgasm, satisfaction, and pain during intercourse were respectively: 89.4%, 87.1%, 69.4%, 68.2%, 77.6%, and 51.8%. The rates of sexual dysfunction in common uterine pathologies among infertile female patients were: polyps (55.2%), fibroids/myomas (64.7%), endometriosis (87.5%); endometrial hyperplasia (45.5%). Conclusion: Infertile female patients with uterine pathology have a high rate of sexual dysfunction. Therefore, it is essential to pay attention to the evaluation during the initial infertility examination to provide appropriate counseling, thereby improving the quality of sexual life and, enhancing the reproductive capabilities of infertile couples.